2014
DOI: 10.1080/09654313.2014.984661
|View full text |Cite
|
Sign up to set email alerts
|

Relations among Clusters

Abstract: Many papers on economic geography have analysed industrial clusters, but few have addressed the relations among clusters. This paper discusses three types of relations among clusters to better understand why they occur and the roles that human resources, capital, knowledge and markets play in such relations. It provides theoretical ideas, empirical illustrations and suggestions for future research on the relations among clusters in a globalized economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
5
0
2
Order By: Relevance
“…In addition to topics of finance and university, and drawing on Lu and Reve (), it is necessary to discuss three situations in particular. In order to simplify the discussion, we assume that there are four clusters: A, B, C, and D. Of these, A, B, and C are the same type of cluster, but D is not.…”
Section: Discussion and Research Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to topics of finance and university, and drawing on Lu and Reve (), it is necessary to discuss three situations in particular. In order to simplify the discussion, we assume that there are four clusters: A, B, C, and D. Of these, A, B, and C are the same type of cluster, but D is not.…”
Section: Discussion and Research Agendamentioning
confidence: 99%
“…Lu and Reve () offered a three‐pronged explanation of why this topic is important. We summarize those three reasons below.…”
Section: Introductionmentioning
confidence: 99%
“…This third model measures the effects of all strong clusters located in a region on the region's economic performance (Delgado et al, 2012, p. 16). This model considers the results of studies noting the relations among clusters (Lu and Reve, 2015).…”
Section: Precision Engineering Clusters Impact On Regional Performancementioning
confidence: 99%
“…In recent years, however, other scholars have embraced the macro-level (that is, multi-cluster level, or relation among clusters) studies. Departing from the business scholars' and geographers' viewpoint, Delgado et al (2010), Bathelt and Li (2014), Li (2014), Lu et al (2013), and Lu and Reve (2015) have shown that conducting studies at a multi-cluster level provides new insights. Some may question whether clusters have relations with one another since they are abstract phenomena (Martin and Sunley, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We argue that just like microeconomics cannot replace macroeconomics, cluster relation summaries based only on the viewpoint of individual firms are insufficient. Furthermore, building on the viewpoint of regional policy makers, who cannot intervene in individual relations, but are interested in how various clusters contribute to economic development, how to balance various clusters' interests is a main issue in regional policy-making (Lu and Reve, 2015).…”
Section: Introductionmentioning
confidence: 99%